ACQUISITION OF LOCAL GOVERNMENT PROPERTY - Michał CHAJDA (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej, 2014)
The aim of the paper is to describe different ways to acquire property by local government units. The authors discusses ways and conditions for the acquisition of local government units and the consequences of such actions in the light of Polish law, the Polish Constitution and international norms.